Extraction and Transport of Amino Acids Using Kryptofix 5 as Carrier through Liquid Membrane - Pankaj Raizada; Uma Sharma (Journal of Chemistry)
The present work explores membrane-mediated extraction and transport studies of amino acids through artificial bulk liquid membrane system with kryptofix 5 as a carrier. The various reaction parameters such as amino acid concentration, carrier concentration, time, pH, and stirring effect were studied to optimize reaction conditions. The stirring of source and receiving phases increased the efficiency of extraction process. Noncyclic receptor kryptofix 5 with five oxyethylene units and terminal aromatic donor end groups governs its transport and extraction efficiency. The extraction and transport efficiency followed the following trend: valine > alanine > glycine > threonine. Supported liquid membrane (SLM) studies were performed using cellulose nitrate, PTFE, eggshell, and onion membranes. The egg shell membrane support proved to be most efficient due to intricate network of water insoluble proteins fibers with very high surface area and homogeneity.